CC-Chemokine receptor CCR7: a key molecule for lymph node metastasis in esophageal squamous cell carcinoma - Irino, Tomoyuki (BioMed Central, 2014)
BACKGROUND: CC-chemokine receptor 7 (CCR7), a known lymph node homing receptor for immune cells, has been reported as a key molecule in lymph node metastasis. We hypothesized a clinicopathological correlation and functional causality between CCR7 expression and lymph node metastasis in patients with esophageal squamous cell carcinoma (ESCC). METHODS: We performed immunohistochemical analysis of 105 consecutive and 61 exclusive pathological T1 ESCC patients, followed by adhesion assay and in vivo experiment using a newly developed lymph node metastasis mouse model. The adhesive ability in response to CC-chemokine ligand 21/secondary lymphoid-tissue chemokine (CCL21/SLC) was assessed in the presence or absence of lymphatic endothelial cells and anti-CCR7 antibody. We established a heterotopic transplantation mouse model and analyzed lymph node metastasis by quantitative real-time RT-PCR. RESULTS: Positive CCR7 expression in immunohistochemistory was detected in 28 (27%) of 105 consecutive patients and 17 (28%) of 61 T1 patients, which significantly correlated with lymph node metastasis (p = 0.037 and p = 0.040, respectively) and poor five-year survival (p = 0.013 and p = 0.012, respectively). Adhesion assay revealed an enhanced adhesive ability of CCR7-expressing cells in response to CCL21/SLC, in particular, in the presence of lymphatic endothelial cells (p = 0.005). In the mouse model, lymph nodes from mice transplanted with CCR7-expressing cells showed significantly higher DNA levels at 5 weeks (p = 0.019), indicating a high metastatic potential of CCR7-expressing cells. CONCLUSION: These results demonstrated the significant clinicopathological relationship and functional causality between CCR7 expression and lymph node metastasis in ESCC patients.